Novel Dermatitis and Relative Viral Nucleic Acid Tissue Loads in a Fin Whale (Balaenoptera physalus) with Systemic Cetacean Morbillivirus Infection. (February 2021) - Dagleish, Mark P.; Perri, Adele; Maley, Madeleine; Ballingall, Keith T.; Baily, Johanna L.; Davison, Nicholas J.; Brownlow, Andrew C.; Rocchi, Mara S.
Summary: Cetacean morbilliviruses (CeMVs) are significant causes of mortality in many cetacean species in epizootics and smaller outbreaks. Despite the prominence of skin lesions in seals and terrestrial animals, including humans, affected by other morbilliviruses, they have not been reported in CeMV-infected cetaceans. Here we report CeMV-associated skin lesions in a fin whale ( Balaenoptera physalus ) with subacute, systemic CeMV infection that live-stranded in Scotland, UK. Grossly, the skin was sloughing in large sheets, presumed due to autolysis, but histological examination showed syncytia, below the dermoepidermal junction, that were strongly immunopositive for morbillivirus antigen, as were syncytia in other organs. By polymerase chain reaction (PCR), the relative load of CeMV-specific RNA was largest in the liver and urinary bladder, even in formalin-fixed, paraffin-wax embedded samples. Levels were low in skin and only detectable in frozen samples. Genetic comparison of the CeMV revealed close alignment with isolates from fin whales from the North Atlantic Ocean and Mediterranean Sea, but that it was distinct from the porpoise CeMV clade. These findings show skin samples can be used to diagnose CeMV infection in cetaceans, highlighting the potential of ante-mortem sampling for monitoring disease in current populations and assessment of changes in host and pathogen genetics.